The Dynamics of Right-Wing Extremism Within German Society: Escape into Authoritarianism - Decker, Oliver (Routledge Studies in Fascism and the Far Right Series, 2022)
The Dynamics of Right-Wing Extremism within German Society explores the prevalence of right-wing extremist attitudes in Germany.